PEMANFAATAN TEKNOLOGI CANVA DALAM PENGEMBANGAN BAHAN AJAR BERBASIS VIDEO DI POS PAUD BINTANG KECIL BALAI KELURAHAN SUMURBOTO, KECAMATAN BANYUMANIK, SEMARANG: PEMANFAATAN TEKNOLOGI CANVA DALAM PENGEMBANGAN BAHAN AJAR BERBASIS VIDEO DI POS PAUD BINTANG KECIL BALAI KELURAHAN SUMURBOTO, KECAMATAN BANYUMANIK, SEMARANG - Netty Nurdiyani; Iswanti; Rio Devilito; Endang Triyani (Bangun Rekaprima, 2026)
To achieve the goal of improving teachers’ competencies, a technology that enables the creation of creative teaching materials is required. One technology widely used today is the Canva application. With this application, learning activities are expected to become more engaging and communicative. To support this aim, a community service program was conducted for the teachers of Pos-PAUD “Bintang Kecil,” focusing on the use of Canva to create comics. The activities were carried out through lectures and hands-on practice. Participants included teachers and several parents who were able to attend. The community service was implemented in several stages: (1) introduction of the facilitators and audience participants, (2) explanation of the Canva application and its benefits in teaching, (3) introduction to Canva features, (4) practice in creating various teaching materials, and (5) monitoring the use of Canva as a teaching medium in the early childhood education setting. During the practice sessions, teachers and parents were assisted by university students participating in the program. Their presence greatly supported and motivated the participants. The teachers felt that the application made it easier to create learning materials aligned with the intended learning objectives.